하상여과 모형에서 수평집수관의 조도계수 - 김우철(Woo Chul Kim); 김승현(Seung Hyun Kim) (Daehan hwan'gyeong gonghag hoeji, 2007)
In order to analyze the experimental results obtained from the model riverbed filtration performed by Ahn et al. a mathematical model was developed to simulate the flow through the lateral. The discharge rates at each section of the lateral measured by Ahn et al. were compared with the model predictions, and they matched favorably. The Manning's roughness coefficients of all the laterals employed in the study of Ahn et al. were determined using the model. Results show that the roughness coefficient becomes larger with the increase in the entrance velocity to the collector well, and that the coefficient ranges from 0.012 to 0.015 under the normal operational conditions of the riverbed filtration. Results also show that the coefficient becomes smaller as the lateral diameter increases. 안 등이 보고한 모형 하상여과정의 수평집수관에 대한 여러 가지 측정치를 해석하기 위해 집수관에서의 흐름을 모사하는 수학적 모델을 개발하였다. 집수관 각 부위에서의 여과수 유입율 측정치와 본 연구에서 개발된 모델 예측치를 비교하였으며, 두 값은 잘 부합하였다. 이 모델을 이용하여 수평집수관 내부의 흐름에 대한 저항 즉, 조도계수를 구했고, 여러 실험조건에서 얻은 집수관의 조도 계수를 분석한 결과 집수정 유입유속이 커짐에 따라 조도계수는 증가하지만 정상적인 하상여과의 경우에는 0.012-0.015로 거의 일정함을 알 수 있었다. 또한, 집수관의 직경이 커지면 조도계수는 감소함을 알 수 있었다.